Effect of Mix Proportions on Strength and Porosity of Pervious Concrete - Bouddh, Avinash; Birali, R. R. L.; Singh, Akhand Pratap (International Journal of Research in Interdisciplinary Studies, 2025)
Pervious concrete, also known as permeable concrete, no-fines concrete, or porous asphalt, is a specialized type of concrete characterized by high porosity, allowing water from precipitation and other sources to pass directly through. This reduces surface runoff and supports groundwater recharge, making it a sustainable material choice for low-impact development. Typically composed of coarse aggregates with little to no fine aggregates, the cement paste coats the aggregates, creating interconnected voids that enable water permeability. This study focuses on evaluating the effect of different mix proportions specifically the variations in water-to-cement (w/c) ratios and coarse-to-fine aggregate (CA:FA) ratios on the mechanical properties and porosity of pervious concrete. Mix designs were developed with w/c ratios ranging from 0.40 to 0.50, and coarse aggregates were varied in proportion to study their impact on compressive and flexural strength. The cement used was OPC 43 grade, with specific gravities of cement, coarse aggregate, and fine aggregate being 3.15, 2.68, and 2.65 respectively. Crushed stone and river sand were used as aggregates. The results aim to identify an optimum mix proportion that ensures both adequate strength and desired porosity. Balancing mechanical strength with permeability is a major challenge in pervious concrete, especially for applications in road pavements. This research contributes to developing a structurally viable and environmentally friendly pavement solution through the proper selection and proportioning of materials.